2010
DOI: 10.1007/s10875-010-9496-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Role of HLA-G in Immune Cells from Patients with Systemic Lupus Erythematosus

Abstract: Human leukocyte antigen (HLA)-G is a class I non-classical HLA molecule with an important regulatory role on the immune response. The possible role of this molecule in the pathogenesis of SLE has not been explored. In this work, we evaluated the expression and function of HLA-G in SLE patients. We studied 37 SLE patients as well as 25 healthy donors. Peripheral blood monocytes and in vitro-generated dendritic cells (DCs) were analyzed for HLA-G expression by flow cytometry. We found that monocytes from SLE pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our results are similar to those of another study showing decreased expression of HLA-G, a non-classical class I HLA molecule with an important role in regulating the immune response, on macrophages/mature dendritic cells and diminished trogocytosis to autologous lymphocytes in patients with SLE [ 41 ]. Many studies have demonstrated that PMNs and lymphocytes coexist and can interact at sites of chronic inflammation, infection, or allergic reactions in vivo [ 13 , 29 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are similar to those of another study showing decreased expression of HLA-G, a non-classical class I HLA molecule with an important role in regulating the immune response, on macrophages/mature dendritic cells and diminished trogocytosis to autologous lymphocytes in patients with SLE [ 41 ]. Many studies have demonstrated that PMNs and lymphocytes coexist and can interact at sites of chronic inflammation, infection, or allergic reactions in vivo [ 13 , 29 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…ILT2 was found to be downregulated in both pDCs and cDCs from SLE patients [216]. Moreover, as the common ligand of these axes, HLA-G was found to be diminished in monocytes from SLE patients, and a compromised ability of these monocytes to inhibit the proliferation of autologous lymphocytes was also revealed [217].…”
Section: Co-signaling Axes In Dendritic Cells (Dcs) Relating To Slementioning
confidence: 99%
“…Rosado and coauthors ( 67 ) and Chen and coauthors ( 68 ) have shown higher sHLA-G and IL-10 levels in systemic lupus erythematosus (SLE) patients in comparison with healthy controls, while Rizzo and coauthors ( 69 ) have observed lower sHLA-G concentrations in SLE patients ( 70 ). Interesting, the analysis of monocytes and mature CD83 positive dendritic cells from SLE patients has evidenced a diminished expression of HLA-G in comparison with healthy controls ( 71 ), a lower HLA-G expression in response to IL-10 and a lower HLA-G trogocytosis from autologous monocytes compared with controls. Using the SNPs mapping approach, HLA-G gene is recognized as a novel independent locus for SLE ( 72 ).…”
Section: Hla-g and Rheumatologic Diseasesmentioning
confidence: 99%